2016
DOI: 10.1016/s2468-2667(16)30002-0
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status and treatment outcomes for individuals with HIV on antiretroviral treatment in the UK: cross-sectional and longitudinal analyses

Abstract: SummaryBackgroundFew studies have assessed the effect of socioeconomic status on HIV treatment outcomes in settings with universal access to health care. Here we aimed to investigate the association of socioeconomic factors with antiretroviral therapy (ART) non-adherence, virological non-suppression, and virological rebound, in HIV-positive people on ART in the UK.MethodsWe used data from the Antiretrovirals, Sexual Transmission Risk and Attitudes (ASTRA) questionnaire study, which recruited participants aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 35 publications
5
62
1
2
Order By: Relevance
“…Data from the UK‐based Antiretrovirals, Sexual Transmission Risk and Attitudes (ASTRA) study again suggest that socioeconomic factors play a role in the observed gender differences in virological responses to ART . Through a survey of participants at eight UK clinics, who had been receiving ART for at least 6 months, the ASTRA study found that women were less likely to have enough money for basic needs than men – one of several socioeconomic factors that was linked to women having a greater likelihood of having a detectable viral load and experiencing viral load rebound after suppression than their male counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…Data from the UK‐based Antiretrovirals, Sexual Transmission Risk and Attitudes (ASTRA) study again suggest that socioeconomic factors play a role in the observed gender differences in virological responses to ART . Through a survey of participants at eight UK clinics, who had been receiving ART for at least 6 months, the ASTRA study found that women were less likely to have enough money for basic needs than men – one of several socioeconomic factors that was linked to women having a greater likelihood of having a detectable viral load and experiencing viral load rebound after suppression than their male counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…Exclusion criteria were as follows: age < 18 years; unable to understand the study questionnaire (available in English or French) because of language or cognitive difficulties; too ill or distressed to complete the questionnaire. Participants self‐completed a confidential paper questionnaire that included items on demographics (gender/sexual orientation; age; ethnicity), socioeconomic factors (UK birth/English fluency; education; employment; housing; financial hardship; supportive network assessed by a modified version of the Duke Functional Social Support questionnaire), HIV‐related factors (stable partner and their HIV status; disclosure of HIV status; ART use; ART start date; ART adherence), health‐related factors (symptoms of depression and anxiety as assessed by the Patient Health Questionnaire, 9 item scale [PHQ‐9] and the Generalized Anxiety Disorder 7 item scale [GAD‐7] , respectively); treatment for depression.…”
Section: Methodsmentioning
confidence: 99%
“…If we fail to address social disadvantage in its many manifestations, we risk exacerbating health inequities. This is not a new phenomenon; the link between income and survival was prospectively observed early in the epidemic (25), nor, as noted by Burch and colleagues, is it limited to HIV (13). Clearly, indirect investments of socioeconomic status will be needed – and as Thoreau notes, these will not come cheap.…”
Section: Commentarymentioning
confidence: 97%
“…In this issue of the Lancet Public Health, Lisa Burch and colleagues (13) reported that among people treated for HIV in the United Kingdom, lower socio-economic status (i.e. financial hardship, non-employment, rented/unstable housing status, and no university education) were strongly associated with HAART non-adherence and virological non-suppression.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation